ANALISIS TINGKAT KETIMPANGAN PENDAPATAN ANTAR KABUPATEN DI PROVINSI ACEH PERIODE 2002-2015 - Rosti Maidar; Raja Masbar; Muhammad Nasir (Syiah Kuala University, 2017)
This study aims to determine the level of income inequality among districts in Aceh Province period 2002-2015. 23 districts / municipalities in Aceh province with the most equitable income per capita with Williamson coefficient below 0.05 is Aceh Singkil, South Aceh, Sabang, Langsa, Subulussalam, Aceh Tamiang, Nagan Raya, Bener Meriah, Gayo Lues, Aceh Tengah , Aceh Barat, Aceh Besar, Bireuen and Aceh Barat Daya. The second order of the District / State level income is fairly evenly evenness and has a value of between .05-.09 coefficient Williamson is Simeulue District, East Aceh, Pidie, North Aceh, Aceh Jaya and Pidie Jaya. Third-placed Regency / City and evenness of their income level is uneven and has a coefficient of 0.10 is above Williamson East Aceh, Lhokseumawe and Banda Aceh. Balance development across the county must be maintained in order to avoid differences in economic progress between districts will ultimately have an impact on the level of welfare of each district.